Effects of caffeine ingestion on exercise testing: A meta-analysis - Doherty, M.; Smith, P. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2004)
This study used the meta-analytic approach to examine the effects of caffeine ingestion on exercise testing. Forty double-blind studies with 76 effect sizes (ES) met the inclusion criteria. The type of exercise test was classified as endurance, graded, or short-term. In comparison with placebo, caffeine improved test outcome by 12.3% (95% CI, 9.1 to 15.4), which was equivalent to an overall ES of 0.41 (95% CI, 0.31 to 0.51). Endurance exercise significantly improved test outcome (P < 0.05) more than either graded or short-term exercise. When exercise protocol was examined, time-to-exhaustion (Tlim) protocols had a significantly greater (P < 0.05) ES than either the graded or the non-Tlim protocol(s). The results from this meta-analysis confirm the ergogenic effects of caffeine, particularly for endurance testing that use Tlim protocols.